EFFECTIVE TOOLS, MECHANISMS AND MEANS OF STATE SUPPORT FOR THE AGRICULTURAL SECTOR - MARTYNIUK, Maksym (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article provides characteristics of the agricultural sector and highlights its priority importance in ensuring food security, socio-economic stability (especially in rural areas), forming export potential, attracting foreign investment and increasing the competitiveness of the national economy. The systemic need, functional features and expected results of state support for the agricultural sector are substantiated. A set of mechanisms for state support for the agricultural sector is determined (institutional, economic, innovation-technological, organizational, market and social), each of which has its own essential characteristics, advantages and disadvantages. In accordance with the proposed mechanisms, a list of instruments and means of state support for the agricultural sector is summarized. It is proved that the distribution of state support mechanisms for the agricultural sector should provide not only for supporting the basic characteristics of the sector’s functioning, such as ensuring access to resources, developing infrastructure or providing financial assistance, but also take into account modern trends to which Ukrainian farmers must quickly adapt in order to achieve stable growth in the conditions of globalization, constant technologization and high uncertainty. It is emphasized that a comprehensive approach to the implementation of state policy in the agricultural sector is required, which involves the implementation of various mechanisms, instruments and means of agricultural policy in order to improve the environment for conducting agriculture in accordance with current challenges and shocks. At the same time, it is important not only to improve coordination between authorities, but also to create clear and transparent rules for providing state aid, ensuring equal conditions for all participants in the agricultural market.